2017
DOI: 10.1007/s00210-017-1398-8
|View full text |Cite
|
Sign up to set email alerts
|

Prostanoid EP3 receptor agonist sulprostone enhances pacemaker activity of colonic interstitial cells of Cajal

Abstract: EP receptor activation by PGE2 regulates gastrointestinal motility by modulating smooth muscle contractility. Interstitial cells of Cajal (ICCs) are pacemaker cells that regulate smooth muscle activity. We aimed to determine effects of the EP3 receptor agonist sulprostone on pacemaker potentials in colonic ICCs. We performed a whole cell patch clamp, RT-PCR, and Ca imaging in cultured ICCs from mouse colon. Sulprostone depolarized the membrane and increased pacemaker frequency. EP3 receptor antagonist blocked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…However, sulprostone had no effects on pacemaker potentials in small intestinal ICC. 21 Thus, in this study, to confirm the functional data of sulprostone, we measured the maximum rate of rise of the resting membrane of pacemaker potentials of colonic ICC. Sulprostone increased the maximum rate of rise of the resting membrane of pacemaker potentials and decreased the duration and interval of pacemaker potentials.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…However, sulprostone had no effects on pacemaker potentials in small intestinal ICC. 21 Thus, in this study, to confirm the functional data of sulprostone, we measured the maximum rate of rise of the resting membrane of pacemaker potentials of colonic ICC. Sulprostone increased the maximum rate of rise of the resting membrane of pacemaker potentials and decreased the duration and interval of pacemaker potentials.…”
Section: Discussionmentioning
confidence: 80%
“… 19 Sulprostone, a PGE 2 ‐EP 3 agonist, also enhanced the pacemaking potential frequency of colonic ICC, and the enhanced effects were blocked by HCN channel blockers. 21 Thus, we suggest that HCN channels are candidate pacemaker channels modulated by endogenous substances in colonic ICC. However, our previous results were mainly obtained using pharmacological studies.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Regarding the EP3 receptor, PGE 2 /EP3 is reported to be associated with the regulation of gastrointestinal motility. (15) Although its exact role is still unknown, it is interesting that EP3 receptors were abundantly seen at the intermuscular plexus. Together with the findings that COX-1 mRNA, COX-2 mRNA, and PG synthases mRNA were mainly observed in the deep duodenal mucosa, the role of prostaglandin for the regulation of visceromotor function might be largely dependent on the EP3 receptor.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we recently reported that the release of PGE 2 by activating TRPA1 channels promotes rectal colon contraction, (14) while the activation of EP3 receptors has been reported to regulate gastrointestinal motility. (15) These reports suggest association of PGE 2 with gastrointestinal motility.…”
mentioning
confidence: 95%